Character emotion experience in virtual environments - Zagalo, Nelson (2008)
The present paper presents an emotion module from an authoring tool of interactive storytelling being developed within the European Project—INSCAPE. The Atmosphere Editor (AE) is an INSCAPE software plug-in. Its aim is to help authors to easily create virtual interactive scenes that are recognized as emotional in order to contribute to higher coherence of their content and simultaneously to emphasize their communication purposes. It works through the attribution of emotional meaning to virtual environments and characters classes that act on the virtual story-world. Therefore, it is designed to produce a semantic intervention in the story but does not intend to transcend the storyteller work. AE presents then a taxonomy capable of sustaining the communicational optimization of the interactive narratives at an emotional level. The AE intervention develops in addition a possible pedagogical virtue permitting the learning by the story authors about potential emotional uses of specific virtual parameters. It permits also the INSCAPE user to understand the emotional semantics canons of the interactive virtual stories.